CARA SISWA TUNA GANDA BERINTERAKSI DENGAN TEMAN SEBAYA DI SLB NEGERI SURAKARTA - Prakosa, Revanka Yoga; Khoirul Hadi, Muhammad; Frans Gennova, Silas Bayu; Suparmi, Suparmi (Jurusan Pendidikan Luar Biasa, 2024)
Children with multiple disabilities have more than two kinds of restrictions that make it hard for them to control themselves and communicate in their surroundings. The objective of this study is to determine how children with multiple disabilities interact with their classmates in school. Descriptive qualitative research with a purpose sampling technique for data collection through observation, interviews, and documentation is used. The researcher himself is the research instrument. Students from SLB Negeri 1 Surakarta were the subjects of the research, with sources from teachers, principals, and deputy school coconuts. Data were tested for validity using triangulation flow of data reduction, presentation, and conclusion drawing. The results of the study showed that there were 2 children with multiple disabilities out of 244 students. 1) blind and emotional and behavioral disorder 2) deaf and mental reterdation. The way of communicating with children with multiple disabilities will adjust to their classification, therefore they often behave differently than they should, due to physical and motor developmental barriers Keywords: Education, Children with Multiple Disabilities, Social Interaction